Device-level modeling and synthesis of high-performance pipeline ADCs - Amaya, Jesus Ruiz- (Springer, 2011)
This book presents models and procedures to design pipeline analog-to-digital converters, compensating for device inaccuracies, so that high-performance specs can be met within short design cycles. These models are capable of capturing and predicting the behavior of pipeline data converters within less than half-a-bit deviation, versus transistor-level simulations.  As a result, far fewer model iterations are required across the design cycle. Models described in this book accurately predict transient behaviors, which are key to the performance of discrete-time systems and hence to the performance of pipeline data converters.  Describes efficient procedures for heirarchical top-down design of pipeline converters;  Presents new methodologies to reduce bottom-up iterations, through inherent embedding of transistor-level parameters, such as parasitic capacitances, transconductances, and saturation currents;   Provides mathematical details of behavioral models, includes descriptions of the synthesis methods and associated tools and illustrates models through case studies supported by silicon prototypes.